PENGARUH KEPRIBADIAN (EKSTROVERT VS INTROVERT) TERHADAP WATER FOOTPRINT SISWA SEKOLAH MENENGAH ATAS DI JAKARTA - I Made Putrawan; Diana Vivanti Sigit; Angela Maria (Universitas Negeri Jakarta, 2016)
The increasing of economic growth evoked the prosperity of its citizen which subsequently would lead to the consumption behaviors of such population for goods andservices. Ecological Footprint is a individual or population as well as the services needed to assimilate west in term of land. Social factors, such as personality, is known as a crucial factor that cause the consumption pattern of individuals is vary considerably. This research was aimed to determine the effect of personality on Ecological Footprint of students at senior high school in Jakarta. Measuring of Ecological Footprint is concentrated on water using at home and school. The activities of water using focused on urinating, defecating, face washing, taking a bath, hand washing, and ritual ablution before Moslem prayers. Water Footprint was calculated from 54 students enrolled in SMAN 107 which are selected acording to simple random sampling, Cakung Jakarta Timur This study was conducted from January to February 2016. The finding indicated that there was no significantly difference between extraversion and intraversion based on their total Water Footprint value.